2010
DOI: 10.1007/s00420-010-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Ocular symptoms, tear film stability, nasal patency, and biomarkers in nasal lavage in indoor painters in relation to emissions from water-based paint

Abstract: House painters may have a risk for adverse physiological reactions in the ocular and nasal mucosa. A minority of painters susceptible to WBP can react with neutrophilic nasal inflammation. Different chemicals in the paint could cause either neutrophilic or eosinophilic inflammation, or reduced tear film stability. In addition, house painters are exposed to MVOC which may affect the nasal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…When employees reoccupied buildings with high levels of MVOCs after flooding, increased signs of eosinophilic inflammation in the nasal mucosae were observed . Similar results were found among professional house painters, for whom exposed to higher levels of 1-octen-3-ol, a known MVOC, was related to reduced nasal patency and increases in nasal-inflammation biomarkers 6 (Wieslander and Norbäck, 2010). Two studies on MVOC exposure and asthma and allergies in schools found a relationship between MVOC exposure and an increased odds ratio (OR) for the occurrence of wheezing, nocturnal breathlessness, doctor-diagnosed asthma, and history of asthma among pupils and among employees (Kim et al, 2007;Smedje et al, 1996).…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangesupporting
confidence: 77%
See 1 more Smart Citation
“…When employees reoccupied buildings with high levels of MVOCs after flooding, increased signs of eosinophilic inflammation in the nasal mucosae were observed . Similar results were found among professional house painters, for whom exposed to higher levels of 1-octen-3-ol, a known MVOC, was related to reduced nasal patency and increases in nasal-inflammation biomarkers 6 (Wieslander and Norbäck, 2010). Two studies on MVOC exposure and asthma and allergies in schools found a relationship between MVOC exposure and an increased odds ratio (OR) for the occurrence of wheezing, nocturnal breathlessness, doctor-diagnosed asthma, and history of asthma among pupils and among employees (Kim et al, 2007;Smedje et al, 1996).…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangesupporting
confidence: 77%
“…MVOC concentrations are higher in buildings that have dampness problems caused by flooding than in control buildings (Wieslander and Norbäck, 2010). These results suggest that exposure to MVOCs is one of the possible effects of dampness.…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 77%
“…Concentrations of SVOCs in indoor air are generally much lower than those of VOCs (Kanazawa et al 2010); however, a number of SVOCs have been detected in indoor dust (Bornehag et al 2005;Meeker and Stapleton 2010;Hoffman et al 2015). In addition, SVOCs, such as plasticizers and flame retardants, have been suggested as causing adverse health effects, including ocular and nasal symptoms and endocrine-disrupting effects (Kojima et al 2009(Kojima et al , 2013Rudel and Perovich 2009;Takeuchi et al 2005b;Wieslander and Norbäck 2010).…”
Section: Introductionmentioning
confidence: 96%
“…PGTex could induce allergic airway inflammation, heightened production of IL-12, and oxidative stress in allergen sensitized mice (41). Occupational exposures to painted surfaces have been associated with eye irritation, skin itching, obstructive airway problems, and frequent urination in a longitudinal follow-up studies (42)(43)(44)(45)(46)(47). To date, US Environmental Protection Agency posed a significant new rule on 14 of PGTex with known risks (48).…”
Section: Home Indoor Dampnessmentioning
confidence: 99%